Inhibition and Adjective Learning in Bilingual and Monolingual Children - Yoshida, Hanako; Tran, Duc N.; Benitez, Viridiana; Kuwabara, Megumi (Frontiers in Psychology, 2011)
The ability to control attention—by inhibiting prepotent, yet no longer relevant information—is an essential skill in all of human learning, and increasing evidence suggests that this ability is enhanced in language learning environments in which the learner is managing and using more than one language. One question waiting to be addressed is whether such efficient attentional control plays a role in word learning. That is, children who must manage two languages also must manage to learn two languages and the advantages of more efficient attentional control may benefit aspects of language learning within each language. This study compared bilingual and monolingual children’s performances in an artificial word-learning task and in a nonlinguistic task that measures attention control. Three-year-old monolingual and bilingual children with similar vocabulary development participated in these tasks. The results replicate earlier work showing advanced attentional control among bilingual children and suggest that this better attentional control may also benefit better performance in novel adjective learning. The findings provide the first direct evidence of a relation between performances in an artificial word-learning task and in an attentional control task. We discuss this finding with respect to the general relevance of attentional control for lexical learning in all children and with respect to current views of bilingual children’s word learning.